Analysis of Knowledge Acquisition in Culinary Business (Case Study of Macaroni Panggang Bogor City) - Muhammadin Innuuridz Wahid; Retno Kusumastuti Hardjono (University of Merdeka Malang, 2021)
This study aims to analyze the process of knowledge acquisition in the culinary business, and the factors that influence knowledge acquisition. This research uses a qualitative approach with a case study method. Case study was selected in this research is Macaroni Panggang, where Macaroni Panggang became one of the culinary businesses that carried out knowledge acquisition on food menus and restaurant management. The data analyzed collected from interviews with owners, supervisors and vice supervisors of Macaroni Panggang. The results of the study found that there are four knowledge acquisition processes in Macaroni Panggang namely planning, taking knowledge, testing stage, and revision stage. Factors that inhibit knowledge acquisition in Macaroni Panggang are human resource factors. At present Macaroni Panggang does not yet have the resources to conduct knowledge acquisition. This makes not all the knowledge taken can be a real product in Macaroni Panggang.